Coherent guided acoustic phonons in GaN/AlN nanowire superlattices. (17th April 2018) - Iwai, Yuki; Mizuno, Seiji
Abstract: We theoretically examine the coherent guided acoustic phonons generated and observed in a GaN/AlN nanowire superlattice by ultrafast pump–probe spectroscopy. We consider the symmetry of the present nanowire superlattice and carry out the variational calculation of dispersion relations. By comparing numerical results with the results approximated using Rytov's equation, we examine the validity of the model used in the experimental explanation. The propagation processes of the guided coherent acoustic phonons previously observed are re-examined on the basis of our numerical results.